Pengaruh Pendidikan dan Pertumbuhan Ekonomi Terhadap Ketimpangan Pendapatan di Indonesia dengan Akses Energi Sebagai Variabel Moderasi: Moderated Regression Analysis - Wahyuni, Ribut Nurul Tri; Utami, Tarisha Althaf (Seminar Nasional Official Statistics, 2024)
Every country, including Indonesia, persistently faces the issue of income disparity. Indonesia's gini ratio in 2022, a measure of income inequality, reached 0.384. We categorize this value as moderate and require efforts to decrease it. One of these efforts is to improve energy access. When combined with other factors, energy access can reduce economic inequality. This study seeks to examine the impact of the interaction between energy access, economic growth, and average years of schooling on income inequality in 34 Indonesian provinces from 2015 to 2022. The study will use moderated regression analysis. According to the research findings, increasing energy availability can mitigate the positive effects of economic growth and average years of schooling on income disparity. Consequently, it is advisable to integrate strategies that foster economic expansion, prolong the average duration of education, and ensure a fair allocation of energy infrastructure, especially in underdeveloped areas. Thus, income disparities will decline.